Solar cell, preparation method thereof and photovoltaic module
By incorporating an ion-blocking layer of an amino-functionalized metal-organic framework material into a perovskite solar cell, the structural damage caused by halide ion migration was resolved, thereby improving the cell's stability and photoelectric conversion performance.
Patent Information
- Application Number
- CN202511471013.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-15
- Publication Date
- 2025-11-11
- Estimated Expiration
- 2045-10-15
AI Technical Summary
The migration of halide ions in perovskite solar cells leads to the destruction of the active layer structure, affecting cell performance and stability and reducing lifespan.
An ion-blocking layer is disposed on at least one side of the perovskite active layer. The ion-blocking layer is composed of a metal-organic framework material (MOF-NH2) with amino functional groups. It adsorbs halogen ions through a porous structure and fixes them through hydrogen bonds to form a barrier and isolation effect.
It effectively suppresses halide ion migration, improves device stability and photoelectric conversion performance, and extends the lifespan of solar cells.
Smart Images

Figure CN120936175A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of photovoltaic cell technology, and in particular to a solar cell and its preparation method, and a photovoltaic module. Background Technology
[0002] Perovskite solar cells have attracted widespread attention due to their many advantages, such as long carrier diffusion length, high absorption coefficient, adjustable band gap, compatibility with multiple fabrication methods, and simple fabrication methods.
[0003] However, halide ion migration is prone to occur in perovskite solar cells, which damages the structure of the perovskite active layer and leads to a decrease in cell performance. At the same time, halide ion migration can also cause the decomposition of perovskite devices and corrosion of electrodes, affecting the stability and lifespan of perovskite solar cells. Summary of the Invention
[0004] Therefore, it is necessary to provide a solar cell and its preparation method, as well as a photovoltaic module, to suppress the migration of halide ions in perovskite solar cells and improve the photoelectric conversion performance, stability, and lifespan of solar cells.
[0005] A first aspect of this application provides a solar cell comprising: a perovskite active layer, the material of which includes ABX3 and the X-site ion includes a halide ion; and an ion blocking layer disposed on at least one side surface of the perovskite active layer along its thickness direction, the ion blocking layer comprising a metal-organic framework material having an amino group.
[0006] In some embodiments, ion blocking layers are disposed on both sides of the perovskite active layer along the thickness direction.
[0007] In some embodiments, the specific surface area of the amino-containing metal-organic framework material is 500 m². 2 / g~2000m 2 / g.
[0008] In some implementations, the thickness of the ion blocking layer is 1 nm to 30 nm.
[0009] In some embodiments, the number of amino functional groups in the organic ligands of the amino-containing metal-organic framework material is greater than or equal to 2.
[0010] In some embodiments, the organic ligands of the amino-containing metal-organic framework material have the following general structural formula: HOOC-L(NH2)2-COOH, where L includes C6~C6. 20 Aromatic hydrocarbons or C6~C substituted with carboxyl groups 20 Aromatic hydrocarbons.
[0011] In some embodiments, the organic ligands of the amino-containing metal-organic framework material include at least one of 2,5-diaminoterephthalic acid, 3,3-diamino-4,4-dicarboxylic biphenyl, the compound shown in formula (1), the compound shown in formula (2), and 2',5'-diamino-[1,1':4',1'']-terphenyl-3,3'',5,5''-tetracarboxylic acid.
[0012] Equation (1); Equation (2).
[0013] In some embodiments, the organic ligands of the amino-containing metal-organic framework material include compounds of formula (3).
[0014]
[0015] Equation (3).
[0016] A second aspect of this application provides a method for fabricating a solar cell, the method comprising the following steps: forming an ion-blocking layer on at least one side surface of a perovskite active layer along its thickness direction; wherein the material of the perovskite active layer includes ABX3, the X-site ion includes a halide ion, and the ion-blocking layer includes a metal-organic framework material having an amino group.
[0017] A third aspect of this application provides a photovoltaic module, which includes the solar cell provided in the first aspect above, or the solar cell prepared by the method of preparing the solar cell provided in the second aspect above.
[0018] Compared with traditional technologies, this application has at least the following beneficial effects: The solar cell provided by this application has an ion blocking layer disposed on at least one side surface of the perovskite active layer. The ion blocking layer includes a metal-organic framework material with amino functional groups (i.e., MOF-NH2 material). The MOF-NH2 material has a tunable porous structure, which can adsorb halide ions while ensuring charge transport. At the same time, the uncoordinated amino groups in the MOF-NH2 material have a passivating effect on the surface of the perovskite active layer and can form hydrogen bond interactions with halide ions, effectively adsorbing and fixing free halide ions that migrate to the surface of the perovskite active layer, inhibiting the migration of halide ions (especially iodide ions) in the perovskite solar cell, forming an effective barrier and isolation effect, thereby improving the stability of the device, and thus improving the photoelectric conversion performance and lifespan of the solar cell. Attached Figure Description
[0019] To better describe and illustrate the embodiments or examples provided in this application, reference may be made to one or more accompanying drawings. Additional details or examples used to describe the drawings should not be considered as limiting the scope of any of the disclosed applications, the currently described embodiments or examples, or the best mode of conduct of these applications as currently understood. Furthermore, the same reference numerals denote the same parts throughout the drawings.
[0020] Figure 1 This is a schematic diagram of the structure of a solar cell in one embodiment of this application.
[0021] Reference numerals: 1. Solar cell; 10. Substrate; 20. First charge transport layer; 30. Ion blocking layer; 31. First ion blocking layer; 32. Second ion blocking layer; 40. Perovskite active layer; 50. Second charge transport layer; 60. Buffer layer; 70. Transparent conductive oxide layer; 80. Metal electrode layer. Detailed Implementation
[0022] Reference will now be made to detailed embodiments of this application, one or more of which are described below. Each example is provided for explanation and not for limitation of this application. In fact, it will be apparent to those skilled in the art that various modifications and variations can be made to this application without departing from its scope or spirit. For example, features described or illustrated as part of one embodiment may be used in another embodiment to produce further embodiments.
[0023] Therefore, this application is intended to cover such modifications and variations falling within the scope of the appended claims and their equivalents. Other objects, features, and aspects of this application are disclosed in or will be apparent from the following detailed description. It will be understood by those skilled in the art that this discussion is merely a description of exemplary embodiments and is not intended to limit the broader aspects of this application.
[0024] In this application, the technical features described in an open-ended manner include both closed technical solutions consisting of the listed features and open technical solutions that include the listed features.
[0025] In this application, numerical ranges are referred to as continuous unless otherwise specified, and include the minimum and maximum values of the range, as well as every value between the minimum and maximum values. Furthermore, when the range refers to integers, it includes every integer between the minimum and maximum values of the range. Additionally, when multiple ranges are provided to describe a feature or characteristic, the ranges may be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges to which they are incorporated.
[0026] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.
[0027] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.
[0028] Unless otherwise specified, all steps of this application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order; for example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.
[0029] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.
[0030] In this article, "aromatic hydrocarbon" refers to an aromatic hydrocarbon group derived from an aromatic ring compound by removing two hydrogen atoms. This group can be monocyclic aryl, fused-ring aryl, or polycyclic aryl; for polycyclic compounds, at least one must be an aromatic ring system. For example, "C6~C..." 20 "Aryl" refers to an aryl group containing 6 to 20 carbon atoms. Each time it appears, it can independently be a C6 aryl, C6 aryl, C6 aryl, or C6 aryl. 10 Aryl, C 14 Aryl, C 18 Aryl or C 20 Aryl groups. Suitable examples include, but are not limited to: benzene, biphenyl, naphthalene, phenylene oxide, pyrene, p-terphenyl and their derivatives.
[0031] The first aspect of this application, as Figure 1 As shown, a solar cell 1 is provided, which includes a perovskite active layer 40 and an ion-blocking layer 30. The perovskite active layer 40 is made of ABX3, and the X-site ion includes a halide ion. The ion-blocking layer 30 is disposed on at least one side surface of the perovskite active layer 40 along the thickness direction, and the ion-blocking layer 30 includes a metal-organic framework material having amino groups.
[0032] The solar cell 1 provided in this application has an ion blocking layer 30 disposed on at least one side of the perovskite active layer 40 along the thickness direction. The ion blocking layer 30 includes a metal-organic framework material (i.e., MOF-NH2 material) with amino functional groups. The MOF-NH2 material has a tunable porous structure, which can adsorb halide ions while ensuring charge transport. At the same time, the uncoordinated amino groups in the MOF-NH2 material have a passivating effect on the surface of the perovskite active layer 40 and can form hydrogen bond interactions with halide ions, effectively adsorbing and fixing halide ions that migrate to the interface of the perovskite active layer 40, inhibiting the migration of halide ions (especially iodide ions) in the perovskite solar cell 1, forming an effective barrier and isolation effect, thereby improving the stability of the device, and thus improving the photoelectric conversion performance and lifespan of the solar cell 1.
[0033] In some embodiments, ion-blocking layers 30 are disposed on both sides of the perovskite active layer 40. During the operation of the solar cell 1, halide ions generally migrate randomly to the upper and lower sides. Therefore, disposing of ion-blocking layers 30 on both sides of the perovskite active layer 40 can protect the bilayer interface of the perovskite active layer 40 and improve the effect of blocking migration.
[0034] In some embodiments, the specific surface area of the amino-containing metal-organic framework material is 500 m². 2 / g~2000 m 2 / g. For example, the specific surface area of a metal-organic framework material with amino groups can be, but is not limited to, 500 m². 2 / g、600 m 2 / g、700 m 2 / g、800 m 2 / g、900 m 2 / g, 1000 m 2 / g、1100 m 2 / g、1200 m 2 / g、1300 m 2 / g, 1400m 2 / g, 1500 m 2 / g、1600 m 2 / g、1700 m 2 / g、1800 m 2 / g、1900 m 2 / g、2000 m 2 / g. The specific surface area of MOF-NH2 materials can indirectly reflect the loading and distribution of amino functional groups, thus affecting pore accessibility and halide ion adsorption efficiency. Therefore, controlling the specific surface area of amino-containing metal-organic framework materials within the above range helps to improve the migration barrier effect of MOF-NH2 materials on halide ions and improve the interfacial stability of the device. Further, the specific surface area of the amino-containing metal-organic framework material is 500 m² / g. 2 / g~1000 m 2 / g.
[0035] In some embodiments, the thickness of the ion blocking layer 30 is 1 nm to 30 nm. Exemplarily, the thickness of the ion blocking layer 30 can be, but is not limited to, 1 nm, 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, and 30 nm. Further, the thickness of the ion blocking layer 30 is 5 nm to 10 nm.
[0036] In some embodiments, the number of amino functional groups in the organic ligands of the amino-containing metal-organic framework material is greater than or equal to two. Thus, the MOF-NH2 material has a multi-amino structure, which forms a more stable coordination structure for halide ions through multi-point hydrogen bonding, thereby enhancing not only the adsorption strength but also the adsorption capacity and improving the migratory barrier effect.
[0037] In some embodiments, the organic ligands of the amino-containing metal-organic framework material have the following general structural formula: HOOC-L(NH2)2-COOH, where L includes C6~C6. 20 Aromatic hydrocarbons or C6~C substituted with carboxyl groups 20 Aromatic hydrocarbons.
[0038] Thus, the aforementioned organic ligands have at least two carboxyl groups and two side-chain amino groups. The terminal carboxyl groups help enhance the coordination ability of the organic ligands with the central metal ion, promote the stable construction of the metal-organic framework, thereby improving the rigidity and film uniformity of the material and enhancing its interfacial adhesion. The side-chain amino groups do not directly participate in the coordination of the central metal ion, but form a more stable coordination structure with halide ions through multi-point hydrogen bonding, which not only enhances the adsorption strength, but also helps to increase the adsorption capacity and improve the effect of blocking migration.
[0039] In some embodiments, the organic ligands of the metal-organic framework material having an amino group include at least one of 2,5-diaminoterephthalic acid, 3,3-diamino-4,4-dicarboxylic biphenyl, the compound shown in formula (1), the compound shown in formula (2), and 2',5'-diamino-[1,1':4',1'']-terphenyl-3,3'',5,5''-tetracarboxylic acid.
[0040] Equation (1); Equation (2).
[0041] In some embodiments, L includes a carboxyl-substituted C6~C 20 Aromatic hydrocarbons. Thus, in addition to the terminal carboxyl group that participates in coordination with the central ion, the above-mentioned organic ligands also have side-chain carboxyl groups. There is a synergistic effect between the side-chain amino group and the side-chain carboxyl group. The side-chain carboxyl group and the side-chain amino group in the organic ligand can interact through the intermolecular hydrogen bond network. For example, when the NH bond of the amino group acts as a hydrogen bond donor to form a hydrogen bond with the oxygen atom of the carboxyl group (NH···O), the polarity of the NH bond is enhanced due to the redistribution of the electron cloud. This makes the hydrogen atom in the NH bond carry a more significant partial positive charge, thereby enabling it to form a stronger electrostatic attraction and a more stable hydrogen bond with the halide ion.
[0042] For example, the organic ligands of metal-organic framework materials having amino groups include compounds of formula (3).
[0043]
[0044] Equation (3).
[0045] In some embodiments, the central metal ion of the amino-containing metal-organic framework material is Zr. 4+ Ti 4+ Cr 3+ Fe 3+ or Zn 2+ Any one of them.
[0046] In some exemplary embodiments, the solar cell 1 includes a substrate 10, a first charge transport layer 20, a first ion blocking layer 31, a perovskite active layer 40, a second ion blocking layer 32, a second charge transport layer 50, a buffer layer 60, a transparent conductive oxide layer 70, and a metal electrode layer 80, which are stacked sequentially.
[0047] In some embodiments, the substrate 10 is a crystalline silicon cell, and the solar cell 1 further includes a tunneling composite layer, which is stacked between the crystalline silicon cell and the first charge transport layer 20.
[0048] The crystalline silicon cell is selected from any one of the following: passivated emitter and back contact cell (PERC), tunnel oxide passivated contact solar cell (TOPCon), heterojunction cell (HJT), interdigitated back contact cell (IBC), heterojunction back contact cell (HBC), and full back contact cell (TBC); when the crystalline silicon cell is used as substrate 10, the solar cell 1 is a tandem cell, and the crystalline silicon cell is used as the bottom cell of the tandem cell to absorb long-wavelength sunlight.
[0049] The tunneling composite layer is made of at least one of indium tin oxide (ITO), indium zinc oxide (IZO), indium tungsten oxide (IWO), and indium zirconium oxide (IZrO). The function of the tunneling composite layer is to recombine electrons and holes from the bottom cell and the hole transport layer.
[0050] In some embodiments, the substrate 10 is conductive glass. Exemplarily, the conductive glass may be FTO conductive glass or ITO conductive glass.
[0051] According to some embodiments of the invention, the first charge transport layer 20 can be a hole transport layer, and the subsequently formed second charge transport layer 50 is an electron transport layer; according to some embodiments of this application, the first charge transport layer 20 is an electron transport layer, and the subsequently formed second charge transport layer 50 is a hole transport layer.
[0052] The materials for the hole transport layer include [2-(9H-carbazole-9-yl)ethyl]phosphonic acid (2PACz), (2-(3,6-dimethyl-9H-carbazole-9-yl)ethyl)phosphonic acid (Me-2PACz), [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid (MeO-2PACz), [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid (4PACz), [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid (Me-4PACz), [4-(3,6-dimethoxy-9H-carbazole-9-yl)butyl]phosphonic acid (Me-4PACz). [N,N-carbazole-9-yl)butyl]phosphoric acid (MeO-4PACz), 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirodifluorene (spiro-OMeTAD), poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA), poly(3,4-ethylenedioxythiophene):poly(4-styrenesulfonate) (PEDOT:PSS), 2,2',7,7'-tetrakis(di-p-tolylamino)spiro-9,9'-difluorene (spiro-TTB), and nickel oxide (NiO) x At least one of the following: The hole transport layer collects holes from the perovskite active layer 40 and blocks the transport of electrons.
[0053] The materials of the electron transport layer include C 60 And at least one of the fullerene derivatives, specifically methyl [6,6]-phenyl-C61-butyrate and methyl [6,6]-phenyl-C71-butyrate (PCBM); the electron transport layer functions to collect electrons from the perovskite active layer 40 and block the transport of holes.
[0054] The perovskite active layer 40 is made of ABX3, where A is a monovalent cation, B is a divalent metal cation, and the X-site ion may include an iodide ion; optionally, the A-site ion includes at least one selected from cesium ion, methylamine ion, ethylamine ion, formamidinium ion, benzylamine ion, and phenethylamine ion; the B-site ion includes at least one selected from lead ion, tin ion, and copper ion; and the X-site ion may also include a bromide ion or a chloride ion. The function of the perovskite active layer 40 is to absorb short-wavelength sunlight and generate photogenerated electron-hole pairs.
[0055] The transparent conductive oxide layer 70 is made of at least one of indium tin oxide (ITO), indium zinc oxide (IZO), fluorine-doped tin oxide (FTO), aluminum-doped zinc oxide (AZO), tungsten-doped indium oxide (IWO), and indium zirconium oxide (IZrO), and is prepared by magnetron sputtering. The function of the transparent conductive oxide layer 70 is to collect charges and transport them laterally to the metal electrode layer 80.
[0056] The material of buffer layer 60 includes tin oxide (SnO). x The buffer layer 60 is at least one of the following: the second charge transport layer 50 and the transparent conductive oxide layer 70; the buffer layer 60 is used to improve the contact between the second charge transport layer 50 and the transparent conductive oxide layer 70 and to avoid damage to the second charge transport layer 50 during the preparation of the transparent conductive oxide layer 70.
[0057] The material of the metal electrode layer 80 includes at least one of Ag, Cu, Al, and Au; the function of the metal electrode layer 80 is to transfer charge to the external circuit.
[0058] A second aspect of this application provides a method for fabricating a solar cell, the method comprising the following steps: forming an ion-blocking layer on at least one side surface of a perovskite active layer along its thickness direction.
[0059] The perovskite active layer is made of ABX3, the X-site ion is a halide ion, and the ion blocking layer is a metal-organic framework material with amino groups.
[0060] In some embodiments, the ion-blocking layer is formed by depositing a precursor solution comprising a metal-organic framework material having an amino group, the concentration of which is 0.1 mg / mL to 5 mg / mL. Exemplarily, the concentration of the precursor solution can be, but is not limited to, 0.1 mg / mL, 0.5 mg / mL, 1 mg / mL, 2 mg / mL, 3 mg / mL, 4 mg / mL, or 5 mg / mL.
[0061] In some of these embodiments, the deposition method includes at least one of spraying or coating.
[0062] In some embodiments, before forming an ion-blocking layer on at least one side of the perovskite active layer, the method further includes the following step: preparing an amino-containing metal-organic framework material. The aforementioned amino-containing metal-organic framework material can be prepared by a solvothermal method. Specifically, an organic ligand, a metal source, and a solvent can be mixed and placed in a reaction vessel for a coordination reaction to form an amino-containing metal-organic framework material. Further specific preparation steps and parameters can be appropriately adjusted according to the type of organic ligand and metal ion selected, and the reaction conditions (temperature, time, solvent, etc.) to obtain a MOF-NH2 material with the target structure and properties for constructing an ion-blocking layer.
[0063] A third aspect of this application provides a photovoltaic module, which includes the solar cell provided in the first aspect above, or the solar cell prepared by the method of preparing the solar cell provided in the second aspect above.
[0064] Multiple solar cells can be arranged, and they can be electrically connected in a single unit or in multiple segments to form multiple cell strings. These cell strings can be connected in series and / or parallel. The photovoltaic module may also include an encapsulation layer and a cover plate. The encapsulation layer covers the surface of the cell strings, and the cover plate covers the surface of the encapsulation layer away from the cell strings. Specifically, in some embodiments, multiple cell strings can be electrically connected through conductive means. The encapsulation layer covers the surface of the solar cells. Exemplarily, the encapsulation layer can be an organic encapsulation film such as an ethylene-vinyl acetate copolymer film, a polyethylene octene co-elastomer film, or a polyethylene terephthalate film. The cover plate can be a glass cover plate, a plastic cover plate, or other light-transmitting cover plate.
[0065] Based on the same inventive concept, embodiments of this application provide a photovoltaic system, including the photovoltaic modules in any of the above embodiments.
[0066] It is understandable that photovoltaic (PV) systems can be applied to PV power plants, such as ground-mounted, rooftop, and floating power plants, as well as to equipment or devices that utilize solar energy for power generation, such as user-installed solar power supplies, solar streetlights, solar-powered cars, and solar-powered buildings. Of course, it is also understandable that the application scenarios of PV systems are not limited to these; that is, PV systems can be applied in all areas that require solar energy for power generation. Taking a PV power grid as an example, a PV system can include PV arrays, combiner boxes, and inverters. A PV array can be a combination of multiple PV modules; for example, multiple PV modules can form multiple PV arrays. The PV arrays are connected to combiner boxes, which collect the current generated by the PV arrays. The collected current then flows through an inverter, converting it into AC power required by the mains grid before being connected to the mains grid to achieve solar power supply.
[0067] The present application will be further described below with reference to specific embodiments and comparative examples.
[0068] Where specific techniques or conditions are not specified in the examples, they shall be performed in accordance with the techniques or conditions described in the literature in this field or in accordance with the product instructions. Reagents or instruments whose manufacturers are not specified are all commercially available conventional products.
[0069] Synthesis Example 1: This synthesis example provides a method for synthesizing the compound shown in formula (1).
[0070]
[0071] Compound a1 (1 eq), 1,3-dibromo-5,5-dimethylhydantoin (DBH, 2 eq), and concentrated sulfuric acid (10 v) were added to a single-necked flask and incubated at 90°C overnight. After cooling to room temperature, ice water was poured in, and the mixture was filtered to obtain a yellow solid 2, which is compound a2. Compound a2 (1 eq), phthalimide (2 eq), and ethanol (10 v) were added to a single-necked flask and incubated at 80°C overnight. After cooling to room temperature, the pH was adjusted to neutral, and the mixture was poured in water and filtered to obtain a solid, which is the compound shown in formula (1).
[0072] Among them, compound a1 is 2,7-pyrene dicarboxylic acid (CAS#: 214622-81-8).
[0073] Synthesis Example 2: This synthesis example provides a method for synthesizing the compound shown in formula (2).
[0074]
[0075] Add compound b1 (1 eq), DBH (2 eq), and concentrated sulfuric acid (10 v) to a single-necked flask, incubate at 90°C overnight, cool to room temperature, pour into ice water, and filter to obtain a yellow solid, which is compound b2; add compound b2 (1 eq), phthalimide (2 eq), and ethanol (10 v) to a single-necked flask, incubate at 80°C overnight, cool to room temperature, adjust the pH to neutral, pour into water, and filter to obtain a solid, which is compound b3; add compound b3 (1 eq), Boc Acid anhydride (2.5 eq) and tetrahydrofuran (10 v) were stirred overnight at room temperature and recrystallized from ethanol to obtain the solid compound b4. Compound b4 (1 eq), sodium borohydride (2.5 eq), and dichloromethane (10 v) were added to a single-necked flask, stirred overnight at room temperature, and recrystallized from ethanol to obtain the solid compound b5. Compound b5 (1 eq) and trifluoroacetic acid (10 v) were added to a single-necked flask, stirred overnight at room temperature, and recrystallized from ethanol to obtain the solid compound shown in formula (2).
[0076] Among them, compound a2 is 2,7-pyrene dicarboxylic acid (CAS#: 214622-81-8).
[0077] Synthesis Example 3: This synthesis example provides a method for synthesizing the compound shown in formula (3).
[0078]
[0079] C1 (1 eq) was added to a two-necked flask along with pinacol diborate (Bpin, 2.5 eq) and [1,1'-bis(diphenylphosphino)ferrocene]palladium dichloride (0.1 eq, Pd(dppf)Cl2). Potassium acetate and toluene were added, and the mixture was heated under reflux for 12 hours under a nitrogen atmosphere. The reaction was complete as shown by TLC. The mixture was cooled to room temperature, concentrated, and purified by column chromatography to give a yellow solid, C2.
[0080] The obtained yellow solids c2 (1 eq) and c3 (2.5 eq) were dissolved in toluene, and tris(dibenzylacetone)palladium (Pd2(dba)3) and tris(o-methylphenyl)phosphine and potassium carbonate solution (2.5 eq) (1 M) were added. Finally, tetra-n-butylammonium bromide (TBAB) was added, and the mixture was heated under reflux for 12 h under a nitrogen atmosphere. The reaction was shown to be complete on TLC. The mixture was cooled to room temperature, filtered, extracted with dichloromethane and water, washed with water, dried, concentrated, and recrystallized from acetone to give white solid c4.
[0081] The obtained C4 (1 eq) was added to a single-necked flask, along with iron powder (10 eq) and ammonium chloride (3 eq), and water. The mixture was stirred at room temperature for 3 hours, and TLC showed no residue. The mixture was filtered, extracted with dichloromethane and water, and washed with water. After drying and concentration, the mixture was recrystallized with acetone. The resulting solid was the compound shown in formula (3).
[0082] Among them, compound c1 is 1,4-dibromo-2,5-dinitrobenzene (CAS#: 18908-08-2); compound c3 is 5-bromobenzene-1,2,4-tricarboxylic acid (CAS#: 13124-84-0).
[0083] Example 1: This example provides a solar cell and its preparation method.
[0084] (1) Cleaning ITO conductive glass: Place the ITO conductive glass in deionized water, anhydrous ethanol and acetone in sequence, and ultrasonically clean for 15 min each, then dry it with N2 for later use.
[0085] (2) Preparation of hole transport layer: Dissolve 2PACz in isopropanol to prepare a 2PACz solution with a concentration of 0.5 mg / mL; spin-coat the 2PACz solution onto the surface of ITO conductive glass to obtain a hole transport layer with a thickness of 1-5 nm.
[0086] (3) Preparation of UiO-66-NH2 material: Weigh 0.3 mmol of ZrCl4 and 0.3 mmol of organic ligand 2-aminoterephthalic acid (H2BDC-NH2), dissolve in 30 mL of dimethylformamide (DMF); transfer the mixed solution to a reaction vessel and react at 120°C for 24 h; wash the product with DMF and methanol three times each, and dry it in a vacuum drying oven at 60°C for 12 h to obtain UiO-66-NH2.
[0087] BET testing shows that the specific surface area of UiO-66-NH2 is 580 m². 2 / g.
[0088] (4) Preparation of the first ion blocking layer: Disperse UiO-66-NH2 powder in isopropanol, sonicate to form a uniform dispersion with a concentration of 1 mg / mL, and deposit the ion blocking layer on the surface of the hole transport layer by spraying; after drying, a first ion blocking layer with a thickness of 10 nm is formed.
[0089] (5) Preparation of perovskite active layer: according to the chemical formula FA of perovskite precursor 0.9 Cs 0.1 Weigh FAI, CsI and PbI2, and dissolve them in 1 mL of a mixed solvent of dimethylformamide and dimethyl sulfoxide (volume ratio 4:1) to obtain a mixed solution with a concentration of 1.6 M. Spin-coat the mixed solution onto the surface of the first barrier layer to obtain a perovskite light-absorbing layer with a thickness of 800 nm.
[0090] (6) Preparation of the second ion barrier layer: Disperse UiO-66-NH2 powder in isopropanol, and ultrasonically treat it to form a uniform dispersion with a concentration of 1 mg / mL. Then, deposit the ion barrier layer on the surface of the perovskite active layer by spraying. After drying, a second ion barrier layer with a thickness of 10 nm is formed.
[0091] (7) Preparation of C 60 Electron transport layer: C is deposited on the surface of the second ion barrier layer via vacuum thermal evaporation. 60 Thin film with a deposition thickness of 15 nm.
[0092] (8) Preparation of SnO x Buffer layer: SnO is deposited on the electron transport layer using atomic layer deposition. x The thickness of the buffer layer is 10nm.
[0093] (9) Preparation of a transparent conductive oxide layer: In SnO x An ITO layer with a thickness of approximately 70 nm was deposited on the buffer layer using magnetron sputtering.
[0094] (10) Preparation of Ag electrode: Ag electrode with a thickness of 110 μm is deposited in the edge region of the device using a thermal evaporation process to form a solar cell.
[0095] Example 2: The solar cell and its preparation method provided in this example are basically the same as those in Example 1, except that in step (3), the reaction temperature is 130℃ and the time is 20 min, and the specific surface area of the UiO-66-NH2 prepared therefrom is 850 m². 2 / g.
[0096] Example 3: The solar cell and its preparation method provided in this example are basically the same as those in Example 1, except that in step (3), the reaction temperature is 200℃ and the time is 30 min, and the specific surface area of the UiO-66-NH2 prepared therefrom is 1180 m². 2 / g.
[0097] Example 4: The solar cell and its preparation method provided in this example are basically the same as those in Example 1, except that in step (3), the organic ligand is replaced with 2',5'-diamino-[1,1':4',1'']-terphenyl-3,3'',5,5''-tetracarboxylic acid, and the MOF-NH2 material prepared thereby has a specific surface area of 1600 m². 2 / g.
[0098] Example 5: The solar cell and its preparation method provided in this example are basically the same as those in Example 1, except that in step (3), the organic ligand is replaced with the compound shown in formula (1), and the specific surface area of the MOF-NH2 material prepared therefrom is 2800 m². 2 / g.
[0099]
[0100] Equation (1).
[0101] Example 6: The solar cell and its preparation method provided in this example are basically the same as those in Example 1, except that step (4) is omitted and step (5) directly prepares the perovskite active layer on the hole transport layer. The solar cell thus prepared has only a second ion blocking layer on the surface of the perovskite active layer near the electron transport layer.
[0102] Example 7: The solar cell and its preparation method provided in this example are basically the same as those in Example 1, except that in step (3), the organic ligand is replaced with the compound shown in formula (3), and the specific surface area of the MOF-COOH-NH2 material prepared therefrom is 3500 m². 2 / g.
[0103]
[0104] Equation (3).
[0105] Comparative Example 1: This comparative example provides a solar cell and its preparation method.
[0106] (1) Cleaning ITO conductive glass: Place the ITO conductive glass in deionized water, anhydrous ethanol and acetone in sequence, and ultrasonically clean for 15 min each, then dry it with N2 for later use.
[0107] (2) Preparation of hole transport layer: Dissolve 2PACz in isopropanol to prepare a 2PACz solution with a concentration of 0.5 mg / mL; spin-coat the 2PACz solution onto the surface of ITO conductive glass to obtain a hole transport layer with a thickness of 2 nm.
[0108] (3) Preparation of perovskite active layer: according to the chemical formula FA of perovskite precursor 0.9 Cs 0.1 Weigh FAI, CsI, and PbI2 and dissolve them in 1 mL of a mixed solvent of dimethylformamide and dimethyl sulfoxide (volume ratio 4:1) to obtain a mixed solution with a concentration of 1.6 M. Spin-coat the mixed solution onto the surface of the hole transport layer to obtain a perovskite light-absorbing layer with a thickness of 800 nm.
[0109] (4) Preparation of C 60 Electron transport layer: C is deposited on the surface of the perovskite active layer via vacuum thermal evaporation. 60 Thin film with a deposition thickness of 12 nm.
[0110] (5) Preparation of SnO x Buffer layer: SnO is deposited on the electron transport layer using atomic layer deposition. x The thickness of the buffer layer is 10m.
[0111] (6) Preparation of a transparent conductive oxide layer: In SnO x An ITO layer with a thickness of approximately 70 nm was deposited on the buffer layer using magnetron sputtering.
[0112] (7) Preparation of Ag electrode: Ag electrode with a thickness of 110 nm is deposited in the edge region of the device by thermal evaporation process to form solar cell.
[0113] Comparative Example 2: This comparative example provides a solar cell and its preparation method.
[0114] (1) Cleaning ITO conductive glass: Place the ITO conductive glass in deionized water, anhydrous ethanol and acetone in sequence, and ultrasonically clean for 15 min each, then dry it with N2 for later use.
[0115] (2) Preparation of hole transport layer: Dissolve 2PACz in isopropanol to prepare a 2PACz solution with a concentration of 0.5 mg / mL; spin-coat the 2PACz solution onto the surface of ITO conductive glass to obtain a hole transport layer with a thickness of 2 nm.
[0116] (3) Preparation of UiO-66 material: Weigh 0.3 mmol of ZrCl4 and 0.3 mmol of organic ligand terephthalic acid (BDC), dissolve them in 30 mL of dimethylformamide (DMF); transfer the mixed solution to a reaction vessel and react at 120°C for 24 h; wash the product with DMF and methanol three times each, and dry it in a vacuum drying oven at 60°C for 12 h to obtain UiO-66.
[0117] BET testing shows that UiO-66 has a specific surface area of 150 m². 2 / g.
[0118] (4) Preparation of the first ion blocking layer: Disperse UiO-66 powder in isopropanol, sonicate to form a uniform dispersion with a concentration of 1 mg / mL, and deposit the ion blocking layer on the surface of the hole transport layer by spraying; after drying, a first ion blocking layer with a thickness of 10 nm is formed.
[0119] (5) Preparation of perovskite active layer: according to the chemical formula FA of perovskite precursor 0.9 Cs 0.1 Weigh FAI, CsI and PbI2, and dissolve them in 1 mL of a mixed solvent of dimethylformamide and dimethyl sulfoxide (volume ratio 4:1) to obtain a mixed solution with a concentration of 1.6 M. Spin-coat the mixed solution onto the surface of the first barrier layer to obtain a perovskite light-absorbing layer with a thickness of 800 nm.
[0120] (6) Preparation of the second ion barrier layer: Disperse UiO-66 powder in isopropanol, sonicate to form a uniform dispersion with a concentration of 1 mg / mL, and deposit the ion barrier layer on the surface of the perovskite active layer by spraying; after drying, a second ion barrier layer with a thickness of 10 nm is formed.
[0121] (7) Preparation of C 60 Electron transport layer: C is deposited on the surface of the second ion barrier layer via vacuum thermal evaporation. 60 Thin film, with a deposition thickness of 12 nm.
[0122] (8) Preparation of SnO x Buffer layer: SnO is deposited on the electron transport layer using atomic layer deposition. x The thickness of the buffer layer is 10nm.
[0123] (9) Preparation of a transparent conductive oxide layer: In SnOx An ITO layer with a thickness of approximately 70 nm was deposited on the buffer layer using magnetron sputtering.
[0124] (10) Preparation of Ag electrode: Ag electrode with a thickness of 110 nm is deposited in the edge region of the device by thermal evaporation process to form solar cell.
[0125] Performance testing: The solar cells fabricated in the above embodiments and comparative examples were placed in a solar simulator (manufacturer: Wavelabs). Under the illumination of a certain solar intensity, a bias voltage (Vp, bias voltage range of -0.1~1.3V) was applied to the device using a test source meter, and the output current of the device was tested to obtain the bias voltage-current density curve.
[0126] Open-circuit voltage (Voc): The terminal voltage of the solar cell when no load is connected, i.e., when the current density in the bias-current density curve is 0 mA·cm. -2 The bias voltage value at that time.
[0127] Short-circuit current density (Jsc): The output current per unit area of the solar cell when it is short-circuited, i.e., the current density when the bias voltage is 0V in the bias voltage-current density curve.
[0128] Fill factor (FF): FF = max(Vp × Jsc), where Vp is the bias voltage and Jsc is the short-circuit current density.
[0129] Photovoltaic cell efficiency (PCE): PCE = Voc × Jsc × FF.
[0130] The initial performance test results and the test results after 1000 hours are shown in Table 1.
[0131] Table 1: Photoelectric performance test results of the examples and comparative examples.
[0132] Initial Voc(V) Voc(V) after 1000 hours <![CDATA[Initial Jsc (mA·cm -2 ).]]> <![CDATA[Jsc (mA·cm after 1000h -2 )]]> Initial FF (%) FF (%) after 1000h Initial PCE (%) PCE (%) after 1000 hours Example 1 1.93 1.91 18.25 18.22 0.82 0.79 28.88 27.49 Example 2 1.94 1.93 18.25 18.23 0.82 0.81 29.03 28.50 Example 3 1.94 1.93 18.25 18.24 0.83 0.81 29.39 28.51 Example 4 1.96 1.95 18.25 18.24 0.83 0.82 29.69 29.17 Example 5 1.97 1.97 18.25 18.24 0.83 0.82 29.84 29.46 Example 6 1.94 1.91 18.25 18.24 0.82 0.79 29.03 27.52 Example 7 1.98 1.97 18.25 18.25 0.83 0.82 29.99 29.51 Comparative Example 1 1.93 1.83 18.25 17.12 0.81 0.66 28.54 20.67 Comparative Example 2 1.94 1.89 18.25 18.13 0.81 0.76 28.68 26.04
[0133] As shown in Table 1, comparing Examples 1-7 and Comparative Examples 1-2, it can be seen that the solar cells provided in this application effectively suppress the migration of halide ions in perovskite solar cells, thereby improving the photoelectric conversion performance and long-term stability of the solar cells.
[0134] The difference between Example 1 and Comparative Example 2 lies in whether the MOF material used in the ion blocking layer contains amino functional groups. As shown in Table 1, although both schemes can improve the photoelectric conversion performance and long-term stability of the device, the MOF material UiO-66 in Comparative Example 2 only forms a physical barrier through its porous structure. Although it can play a certain role in ion blocking, its open-circuit voltage Voc still showed a significant decrease of 0.05V after 1000 hours, indicating that simple physical encapsulation and adsorption cannot solve the non-radiative recombination problem caused by interface defects and ion migration. In this application, by introducing amino functional groups into the MOF material, amino groups can effectively passivate defects on the perovskite surface and anchor halide ions through hydrogen bonding. Through the synergistic effect of physical blocking, chemical passivation, and anchoring, the long-term stability of the perovskite solar cell is improved. Specifically: the Voc of Example 1 decreased by only 0.02V after 1000h, and its stability far exceeded that of Comparative Example 2; the PCE of Example 1 maintained a retention rate of 95.19% after 1000h, which was much higher than the 90.79% of Comparative Example 2, and significantly reduced the degradation of photoelectric performance.
[0135] The difference between Example 1 and Example 7 lies in the type of organic ligand. Although both use MOF-NH2 material, the organic ligand used in Example 7 contains both side-chain carboxyl and side-chain amino groups. These side-chain carboxyl and amino groups can form hydrogen bonds, affecting the electron cloud arrangement of the amino group and thus enhancing the electrostatic adsorption and bonding of halide ions. In Example 1, the carboxyl group in the organic ligand only coordinates with the central metal ion and does not possess the aforementioned effect. Therefore, as shown in Table 1, Example 7 exhibits better open-circuit voltage, short-circuit current density, fill factor, and photoelectric conversion efficiency than Example 1, and its decay rate is slower, demonstrating the synergistic effect of the side-chain amino and carboxyl groups.
[0136] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0137] The embodiments described above are merely illustrative of several implementation methods of this application, and while the descriptions are specific and detailed, they should not be construed as limiting the scope of this patent application. It should be noted that those skilled in the art can make various modifications and improvements without departing from the technical concept of this application, and these modifications and improvements all fall within the protection scope of this application. Therefore, the protection scope of this application should be determined by the appended claims.
Claims
1. A solar cell, characterized in that, include: The perovskite active layer, wherein the material of the perovskite active layer includes ABX3, and the X-site ions include halide ions; and An ion blocking layer is disposed on at least one side surface of the perovskite active layer along the thickness direction, the ion blocking layer comprising a metal-organic framework material having amino groups. The organic ligands of the metal-organic framework material containing amino groups have the following general structural formula: HOOC-L(NH2)2-COOH, where L includes C6~C6. 20 Aromatic hydrocarbons or C6~C substituted with carboxyl groups 20 Aromatic hydrocarbons.
2. The solar cell according to claim 1, characterized in that, The ion blocking layer is disposed on both sides of the perovskite active layer along the thickness direction.
3. The solar cell according to claim 1, characterized in that, The specific surface area of the amino-containing metal-organic framework material is 500 m². 2 / g~2000 m 2 / g.
4. The solar cell according to claim 1, characterized in that, The thickness of the ion blocking layer is 1 nm to 30 nm.
5. The solar cell according to claim 1, characterized in that, The organic ligands of the metal-organic framework material having amino groups include at least one of 2,5-diaminoterephthalic acid, 3,3-diamino-4,4-dicarboxylic biphenyl, the compound shown in formula (1), the compound shown in formula (2), and 2',5'-diamino-[1,1':4',1'']-terphenyl-3,3'',5,5''-tetracarboxylic acid; Equation (1); Equation (2).
6. The solar cell according to claim 1, characterized in that, The organic ligands of the metal-organic framework material having amino groups include compounds of formula (3): Equation (3).
7. A method for preparing a solar cell, characterized in that, Includes the following steps: An ion-blocking layer is formed on at least one side of the perovskite active layer along the thickness direction; The perovskite active layer is made of ABX3, the X-site ion includes at least a halide ion, and the ion blocking layer comprises a metal-organic framework material with amino groups.
8. A photovoltaic module, characterized in that, This includes solar cells as described in any one of claims 1 to 6, or solar cells prepared by the method described in claim 7.
Citation Information
Patent Citations
Ni-MOF hole transport layer based on Ni-MOF framework, perovskite solar cell and preparation method of perovskite solar cell
CN116419581A
Metal organic framework material, preparation method thereof and perovskite battery
CN119823402A
MOF and manufacturing method thereof, solar cell and manufacturing method thereof, power generation device and power utilization device
CN120309952A
Solar cell and preparation method thereof, power utilization device and power generation device
CN120614932A
Solar cell and preparation method thereof, power utilization device and power generation device
CN120614937A